'NO! We don't have a joint account': mobile telephony, mBanking, and gender inequality in the lives of married women in western rural Kenya. Issue 14 (26th October 2022) - Komen, Leah Jerop; Ling, Richard
ABSTRACT: This paper examines how mobile communication and mobile banking is used by women in rural western Kenya (Elgeyo Marakwet), a resource-constrained area where women must carefully monitor the flow of money through their households. Also, women face structural inequality. Among other things, polygyny (one husband and several wives) is legal. Based on the inductive analysis of 25 interviews with women, and using the lens of intersectionality, we examine their use of mobile banking. We examine how mobile technology plays into the management of the household economy, and how it is used in extramarital relationships. We discuss how women use mobile communication in their collective savings groups ( chama ). We see how the mobile phone can be the locus of tensions within the household and how mBanking both supports the lives of the women but also how this can eventually undercut social support.